Advances in clinical chemistry. (Advances in Clinical Chemistry., 2007)
Volume forty-four of the Advances in Clinical Chemistry series contains review articles of wide interest to clinical laboratory scientists and diagnostic adventurers. Articles in this volume cover such topics as Caspases in Myocardial Infarction; Deamidated Gliadin Peptides as Targets for Celiac Disease Specific Antibodies; Urokinase Receptor Variants in Tissue and Body Fluids; Proteomics in Cancer; Paraneoplastic Neurological Syndromes and Oncnerual Antibodies: Clinical and Immunological Aspects; Pathophysiologic Mechanisms of Angiogenesis; Bikunin (Urinary Trypsin Inhibitor): Structure, Biological Relevance and Measurement; and Gene Expression Assays.